The impact of the Inca Empire in Northwest Argentina: Assessment of health status and food consumption at Esquina de Huajra (Quebrada de Humahuaca, Argentina) - (:unkn) unknown (John Wiley & Sons Ltd, 2018)
The Inca Empire annexed the modern territory of Northwest Argentina ca. 1450 AD. Inca presence manifested regionally with different intensity, highlighting that the Empire carried out different strategies when interacting with conquered populations even within the same region. Regional fluctuations in power centralization may affect the quality of life of local groups, regarding accessto food, labour, conflict, or inequality. In this paper, we analyse stable isotopes, dental, and osteological information to evaluate if the individuals that inhabited the archaeological site Esquina de Huajra (Quebrada de Humahuaca, Jujuy) experienced a deprived life quality under Inca administration.Isotopic results signal a balanced diet composed of both vegetal and animal resources, and skeletal indicators of health do not suggest a population undergoing stress.

Gheggi, M. S., Williams, V. I. y Cremonte, M. B. (2018). The impact of the Inca Empire in Northwest Argentina: Assessment of health status and food consumption at Esquina de Huajra (Quebrada de Humahuaca, Argentina). International Journal of Osteoarchaeology, 28(3), 274-284.
Fil: Gheggi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad Nacional de La Rioja; Argentina. Universidad Nacional de Catamarca; Argentina. Secretaría de Industria y Minería. Servicio Geológico Minero Argentino; Argentina
Fil: Williams, Verónica Isabel. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Fil: Cremonte, María Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad Nacional de Jujuy. Instituto de Ecorregiones Andinas; Argentina
Keywords: Bioarchaeology; Empires; Inca; Northwest Argentina